The Swiss family Robinson - Wyss, Johann David 1743-1818. (Mineola, N.Y. Dover Publications, 2001)
When a Swiss couple and their four sons are shipwrecked on an isolated island, they adapt to their "New Switzerland" using many imaginative methods of farming and animal taming.
"This Dover edition, first published in 2001, is an unabridged republication of a standard English-language edition of the work originally published in German in 1812-13 by Johann Rudolf Wyss, a son of the author, and published in 1889 in an altered English-language edition edited by W.H.G. Kingston"--T.p. verso.
Keywords: Family life -- Fiction; Survival -- Fiction; Islands -- Fiction